“On the High Seas with no Place to Land”: The Smyrnaean Inferno and Humanitarian Aid to Armenian and Greek Refugees from Turkey (1922-1923) - Chabot, Joceline; Kasparian, Sylvia (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
In September 1922, the great fire of Smyrna drove more than 200,000 Armenian and Greek refugees to the wharves of that port city. They had fled to Smyrna to escape the massacres perpetrated by Turkish nationalist troops and now urgently needed humanitarian aid to relocate them to safety in Greece. In this article we examine the actions and the roles of humanitarian workers of the Near East Relief (NER) and the American Women’s Hospitals (AMH) working in Greece among these refugees deported from Smyrna. We highlight the central role of women doctors and nurses in their humanitarian efforts to save this population. Their actions, and the gratitude of their peers and government authorities, solidified their professional status in the context of profound changes to transnational humanitarianism after 1919.
Keywords: Armenian genocide; Political science; Sociology; Literature; Law